Intracellular S1P Levels Dictate Fate of Different Regions of the Hippocampus following Transient Global Cerebral Ischemia. (1st August 2018) - Rashad, Sherif; Niizuma, Kuniyasu; Saigusa, Daisuke; Han, Xiaobo; Sato-Maeda, Mika; Saito, Ritsumi; Uruno, Akira; Fujimura, Miki; Ikawa, Shuntaro; Yamamoto, Masayuki; Tominaga, Teiji
Highlights: S1P is a pro-survival sphingolipid that is involved in a wide range of cellular processes. S1P is synthesized by kinases, exported by Spinster 2 and degraded by S1P lyase. CA1 hippocampal region is especially vulnerable to tGCI. Several mechanisms have been implicated in this vulnerability. S1P was upregulated early in CA3 region after tGCI and not CA1, indicating a lack of neuroprotection in CA1. Spinster 2 was downregulated in CA3 after tGCI coinciding with S1P increase, indicating an S1P conservation mechanism. Abstract: Sphingosine-1-phosphate (S1P) is a sphingolipid molecule produced by the action of sphingosine kinases (SphK) on sphingosine. It possesses various intracellular functions through its interactions with intracellular proteins or via its action on five G-protein-coupled cell membrane receptors. Following transient global cerebral ischemia (tGCI), only the CA1 subregion of the hippocampus undergoes apoptosis. In this study, we evaluated S1P levels and S1P-processing enzyme expression in different hippocampal areas following tGCI in rats. We found that S1P was upregulated earlier in CA3 than in CA1. This was associated with upregulation of SphK1 in both regions; however, SphK2 was downregulated quickly in CA3. S1P lyase was also downregulated in CA3, but not in CA1. Spinster 2, the S1P exporter, was upregulated early in both regions, but was quickly downregulated in CA3. Together, these effects explain the variable levels of S1P in the CA1 and CA3 areas and indicate that S1P levels play a role in the preferential resistance of the CA3 subregion to tGCI-induced ischemia. FTY720 did not improve neuronal survival in the CA1 subregion, indicating that these effects were due to intracellular S1P accumulation. In conclusion, the findings suggest that intracellular S1P levels affect neuronal cell fate following tGCI.